Cyber Security Behavior of IT Students: An Example of EMU - Lawal, Sijuwonuola Tolu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Due to technological innovations, the world has changed and everything such as information is easily accessible in electronic and digital format. This has revealed the importance of the concept of cyber security. The main purpose of this thesis is to examine the cyber security behaviors of Eastern Mediterranean University (EMU) Information Technology (IT) undergraduate students. In the study, cyber security behaviors were examined according to 5 sub-dimensions: malware, password usage, phishing, social engineering, and online scam. In addition, this study determines the relationship between cyber security behavior of IT students and their gender. Cyber Security Behavior (CSB) Scale (Muniandy, Muniandy, & Samsudin, 2017) was used as a data collection tool in the research. The study was carried out using the quantitative research method and survey model. Participants of the study consisted of 255 IT undergraduate students who enrolled at EMU in the spring semester of 2018- 2019. The results of this research show that IT undergraduate students have generally low cyber security behaviors. In addition, when all sub-dimensions were evaluated, it was determined that IT undergraduate students had low cyber security behaviors in the sub dimensions of malware, password usage, social engineering, and online scam. Only, IT undergraduate students had high cyber security behavior in the phishing sub dimension. In addition, IT undergraduate students had the lowest cyber security behavior in the social engineering sub-dimension, and the highest cyber security behavior in the phishing sub-dimension. Subsequently, the findings of this research show that a significant difference exists between IT students’ cyber security behavior and their gender. Male IT undergraduate students demonstrated higher cyber security behaviors than female’s IT undergraduate students in 6 Items, while female IT students demonstrated higher cyber security behaviors than male IT students in 2 Items out of 50 items.

ÖZ: Özellikle teknoloji alanında yaşanan yenilikler nedeniyle tüm dünyada hızlı değişimler oluşmaktadır. Günümüzde bilgiye elektronik ve dijital formatta kolayca erişilebilir bir ortam oluşmuştur. Bu gelişmeler, siber güvenlik kavramının önemini de ortaya çıkartmıştır. Bu tez çalışmasının temel amacı, Doğu Akdeniz Üniversitesi (DAÜ), Bilgi Teknolojileri (BT) lisans programı öğrencilerinin siber güvenlik davranışlarının incelenmesidir. Çalışmada, öğrencilerin siber güvenlik davranışları, 5 alt boyuta (kötü amaçlı yazılım, parola kullanımı, kimlik avı, sosyal mühendislik ve çevrimiçi dolandırıcılık) göre incelenmiştir. Ayrıca bu çalışmada bir diğer amaç olarak, BT öğrencilerinin siber güvenlik davranışları ile cinsiyetleri arasındaki ilişki de araştırılmıştır. Araştırmada veri toplama aracı olarak, Siber Güvenlik Davranış (CSB) Ölçeği (Muniandy, Muniandy ve Samsudin, 2017) kullanılmıştır. Çalışma nicel araştırma yöntemi temel alınarak ve tarama modelinden yararlanılarak gerçekleştirilmiştir. Çalışmanın katılımcılarını, DAÜ'de 2018-2019 bahar döneminde kayıt yaptıran 255 BT lisans öğrencisi oluşturmuştur. Çalışma sonucunda, BT lisans öğrencilerinin genel olarak düşük siber güvenlik davranışlarına sahip olduğu belirlenmiştir. Ayrıca, tüm alt boyutlar açısından değerlendirildiği zaman, BT lisans öğrencilerinin kötü amaçlı yazılım, parola kullanımı, sosyal mühendislik ve çevrimiçi (e-) dolandırıcılık alt boyutlarında düşük siber güvenlik davranışlarına sahip oldukları, kimlik avı alt boyutunda ise siber güvenlik davranışlarının yüksek olduğu tespit edilmiştir. Ek olarak, BT lisans öğrencilerinin sosyal mühendislik alt boyutunda en düşük siber güvenlik davranışına sahip olduğu, çevrimiçi (e-) dolandırıcılık alt boyutunda ise en yüksek siber güvenlik davranışına sahip olduğu görülmüştür. Ayrıca, bu araştırmanın bulguları arasında, BT lisans öğrencilerinin siber güvenlik davranışları ile cinsiyetleri arasında da bir fark olduğunu ortaya koyulmuştur. Toplam 50 maddeden oluşan CSB ölçeğinin, 2 maddesinde kadın BT lisans öğrencilerinin daha yüksek siber güvenlik davranışı sergilediği belirlenirken, 6 Madde de erkek BT lisans öğrencilerinin daha yüksek siber güvenlik davranışları gösterdiği tespit edilmiştir.
Master of Science in Information and Communication Technologies in Education. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technology, 2021. Supervisor: Prof. Dr. Ersun İşçioğlu
Keywords: Computer Education and Instructional Technology Department; Information and Communication Technologies in Education; Computer Security--Data security; Education--Information and Communication Technologies--IT Students--Cyber Security; Cyber security, cyber security behavior, malware, phishing, online scam, social engineering